Cooperativity of Catechols and Amines in High‐Performance Dry/Wet Adhesives. Issue 38 (30th July 2020) - Tiu, Brylee David B.; Delparastan, Peyman; Ney, Max R.; Gerst, Matthias; Messersmith, Phillip B.
Abstract: The outstanding adhesive performance of mussel byssal threads has inspired materials scientists over the past few decades. Exploiting the amino‐catechol synergy, polymeric pressure‐sensitive adhesives (PSAs) have now been synthesized by copolymerizing traditional PSA monomers, butyl acrylate and acrylic acid, with mussel‐inspired lysine‐ and aromatic‐rich monomers. The consequences of decoupling amino and catechol moieties from each other were compared (that is, incorporated as separate monomers) against a monomer architecture in which the catechol and amine were coupled together in a fixed orientation in the monomer side chain. Adhesion assays were used to probe performance at the molecular, microscopic, and macroscopic levels by a combination of AFM‐assisted force spectroscopy, peel and static shear adhesion. Coupling of catechols and amines in the same monomer side chain produced optimal cooperative effects in improving the macroscopic adhesion performance. Abstract : Making it stick : The design and synthesis of amino‐catechol adhesives by copolymerization of traditional monomers with mussel‐inspired monomers is presented. The coexistence of catechol and amine moieties in a hybrid monomer architecture can lead to optimization of the overall performance of the catechol–amine adhesives and the development of pressure‐sensitive adhesives with remarkable resistance to flow under shear.